Factors Affecting Medical Students’ Performance in Reading Text - Sihombing, Debora Mei Sawita; Br Sembiring, Yenita; Elpriska (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2024)
Medical students must be able to read English texts in order to have a broader understanding. However, there are a number of obstacles that medical students face when reading English texts, preventing them from achieving the goal of reading—to expand one's knowledge. The purpose of this study was to find out what influences medical medical students ability to read English texts. In this study, questionnaires were used for quantitative research. Syntax, vocabulary, word meaning, sociocultural knowledge, nervousness, and time pressure are among the factors that influence medical students ability to read English texts, according to the findings of this study. To improve medical medical students ability to read English texts, the findings of this study suggested that specific aspects must be focused on and taken into consideration.